A MANAGEMENT AUDITOR INDEPENDENCE ON AUDIT QUALITY AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE IDX (2013-2016)” - Aginta , Windy; Safriandi, Ferry; Pasaribu, Aria Masdiana (Jurnal Ekonomi, 2022)
The objectives of this study were to find out the positive effect of audit tenure, auditor rotation, KAP size, and auditor independence on audit quality partially and simultaneously in manufacturing companies listed on the IDX and to find out whether audit fees can strengthen or weaken the relationship between audit tenure, auditor rotation, KAP size, auditor independence on audit quality in manufacturing companies listed on the IDX. This study uses an associative method. The data source used is secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) with 14 samples of manufacturing companies in the food and beverage sector and the observation year for 4 years. The data will be analyzed with the data analysis conducted, it is concluded that testing using the logistic regression method, the results of this study indicate that audit tenure, auditor rotation, KAP size and audit independence have no effect on audit quality and based on testing using the residual test, the results of this study indicate that audit fees are not significant in moderating the relationship between audit tenure, auditor rotation, KAP size and auditor independence on audit quality.